The Effectiveness of Communication Ethics in Achieving Learning Objectives at State Vocational High School 4 Makassar - Sufriadi, Sufriadi; Yuni, Neneng Patri; Jamaluddin, Jamaluddin; Kasmita, maya (Jurnal Office, 2018)
This study aims to determine the effectiveness of communication ethics in achieving learning goals at SMK Negeri 4 Makassar. This research is descriptive qualitative with a description of the focus on honesty, mutual understanding, obligation to care (well-being), confidentiality, and consequences. The number of informants in this study were five people consisting of principals, deputy principals, subject teachers, and two female students at Makassar State Vocational High School 4. The sample technique used was purposive sampling by sampling data sources based on certain considerations. Data collection was carried out by observation, interview, and documentation techniques. The results of the study showed that the ethics of communication in achieving learning objectives at SMK Negeri 4 Makassar were effective. This can be seen from the five aspects of behavioral guidance in building communication ethics, namely honesty, mutual understanding, obligation to care (well-being), confidentiality and consequences.